2017
DOI: 10.1111/cas.13334
|View full text |Cite
|
Sign up to set email alerts
|

Double‐edged sword of mesenchymal stem cells: Cancer‐promoting versus therapeutic potential

Abstract: Mesenchymal stem cells (MSCs) derived from adipose tissue, bone marrow, cord blood, and other tissues, have recently attracted much attention as potential therapeutic agents in various diseases because of their trans‐differentiation capacity. However, recent studies have suggested that MSCs also appear to contribute to tumor pathogenesis by supporting tumor microenvironments, increasing tumor growth, and eliciting antitumor immune responses. Although some studies suggest that MSCs have inhibitory effects on tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
131
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(147 citation statements)
references
References 104 publications
2
131
1
6
Order By: Relevance
“…On the negative side, MSCs are the cultured product of a heterogeneous mixture of unseparated cells, and in vitro growth involves cell exposure to animal proteins, hence chances of xenogeneic immunization, and entails risks of bacterial contamination and genetic instability. There have been occasional reports of MSC malignant transformation [51]; principally, it is increasingly accepted that MSC recruitment to the tumor stroma can favor cancer development [52]. For all these reasons, it might be beneficial to use purified, non-cultured perivascular cells in place of culture-derived MSCs for cell therapies.…”
Section: Discussionmentioning
confidence: 99%
“…On the negative side, MSCs are the cultured product of a heterogeneous mixture of unseparated cells, and in vitro growth involves cell exposure to animal proteins, hence chances of xenogeneic immunization, and entails risks of bacterial contamination and genetic instability. There have been occasional reports of MSC malignant transformation [51]; principally, it is increasingly accepted that MSC recruitment to the tumor stroma can favor cancer development [52]. For all these reasons, it might be beneficial to use purified, non-cultured perivascular cells in place of culture-derived MSCs for cell therapies.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, they have been tested as a potential therapy for different conditions including T1D . However, an important concern regarding the use of MSCs is that they convey a not inconsiderable risk of carcinogenesis, as well as the possibility that they maldifferentiate into cell types that may exacerbate the phenotype . It is expected that treatment with exosomes isolated from MSCs will greatly decrease the risk of carcinogenesis and maldifferentiation, as they lack a genome and autoreplication properties.…”
Section: Exosomes As Therapy For Diabetesmentioning
confidence: 99%
“…However, debate is still on regarding the impact of MSCs on tumor growth. Many studies have shown pro-tumoral effects while just as many have demonstrated the opposite [48, 49]. The unavailability of good humanized animal models allowing to study the interaction between a human tumor and autologous immune cells has prevented researchers from measuring the potential impact of MSCs on tumor growth through alterations of the immune response.…”
Section: Introductionmentioning
confidence: 99%